Argumentos de densidad y el lema de Kronecker - Caminha, Antonio (Universidad Antonio Nariño, 2023)
These notes discuss the concept of density in the set of real numbers, withspecial emphasis on Kronecker’s lemma and some of its interesting applications.In general lines we follow reference [1].